Wireless Mesh Networks Security, Architectures and Protocols - Khatib, Mutamed; Alsadi, Samer (IntechOpen, 2020)
The book discusses a very promising and effective approach in wireless communications called Wireless Mesh Networks (WMN) and its related issues. Meshes with external access capability, i.e. connected to the Internet, will be discussed. A full overview of WMNs with a technical assessment of mesh and multi-hop networking will be highlighted. Chapters in this book will provide a clear overview and summary and will evaluate some practical examples of upright mesh applications.